Problems and Solutions of Implementing Religious Moderation in the Era of Social Media and Modernity - Rahmawati, Ailsa (Riviera Publishing, 2025)
Indonesia, with the world's largest Muslim population and highly diverse society, faces significant challenges in implementing religious moderation amid rapid digital transformation. With internet penetration reaching 78.19% in 2023, social media has become a battleground for religious narratives, amplifying both moderate and extreme ideologies. This study aims to comprehensively identify the problems and formulate strategic solutions for implementing religious moderation in the social media era. Using a qualitative approach with descriptive-analytical methods, this research employs library research strengthened by content analysis of religious narratives on social media platforms during 2020-2025. The study reveals five fundamental problems: algorithmic architecture that promotes polarizing content, disparity in virality between moderate and extreme content, acceleration of hoax and hate speech dissemination, low digital literacy, and fragmentation of religious authority. The findings indicate that effective solutions must integrate five strategic pillars: optimization of engaging yet substantive content strategies, community-based digital literacy strengthening, multi-stakeholder collaboration, contextual pedagogical innovation, and development of sustainable moderate content ecosystems. This research confirms that religious moderation in the digital era requires reinterpretation of classical wasathiyyah principles into digital communication strategies aligned with attention economic logic and algorithmic amplification. The study offers a measurable implementation roadmap with specific targets, key stakeholders, success indicators, and realistic timeframes, considering that success depends on government political will, commitment of religious institutions, willingness of technology platforms to collaborate, and active civil society participation.